Portable Extendable Dining Table - Mohamad, Mahmod Abd Hakim; Amir Safwan Ismail,; Nurfarahin Onn,; Ahmad Basri Adnan,; Muhammad Shahrul Zulkeflee,; Abdullah Wagiman,; Tuan Mohd Hafeez Tuan Ibrahim, (Multidisciplinary Applied Research and Innovation, 2024)
Semi-Automatic Folding Dining Table is a versatile furniture piece designed to maximize space efficiency in modern livingRapid urban expansion and the prevalence of small living spaces present a challenge for city dwellers seeking space-efficient and versatile furniture. This research project revolves around developing and evaluating a Portable Extendable Dining Table tailored to the specific needs of small house residents. The project's objectives encompass crafting a functional portable extendable dining table and conducting comprehensive calculations and simulations for this table. The project's scope includes designing a table with a maximum load capacity of 55 kg, suitable for flat surfaces, featuring a mechanical system based on gears and linkages, primarily for opening and closing the table flaps. Materials employed comprise rubberwood for the table's body, linkages, and gears for the mechanism, caster wheels for mobility, and a shunt DC motor for power. The methodology encompasses multiple aspects, including defining project functions, material selection, conceptual design, cost estimation, and more. Key findings indicate a favourable reception of the Portable Extendable Dining Table among small house residents, thanks to its adaptability and convenience, with a clear trend favouring sleek, minimalist designs and user-friendly extension mechanisms. The discussion emphasizes the significance of functionality analyses. Future work may focus on enhancing the mechanical system, refining the overall design, and incorporating smart features, making the Portable Extendable Dining Table a promising solution for those in compact living spaces.